Design, synthesis and in vitro biological activities of coumarin linked 1,3,4-oxadiazole hybrids as potential multi-target directed anti-Alzheimer agents - Namy George; Bushra Al Sabahi; Majed AbuKhader; Khalid Al Balushi; Md. Jawaid Akhtar; Shah Alam Khan (Journal of King Saud University: Science, 2022)
Introduction: Alzheimer’s disease (AD) is one of the most common and prevalent forms of neurodegenerative diseases. Coumarin is a versatile scaffold that exhibits a wide range of biological properties including cholinesterase inhibitory activity and therefore is an important heterocyclic moiety to develop anti-AD drugs. Objectives: This study aimed to design and synthesize coumarin linked 1,3,4-oxadiazole hybrid derivatives as multi-target directed ligands (MTDLs) and to investigate their in vitro anticholinesterase, antioxidant and anti-inflammatory activities. Methods: Two series (4a-n and 7a-m) of low molecular weight ligands (27 compounds) containing coumarin linked 1,3,4-oxadiazole hybrids were synthesized and their chemical structures were characterized using analytical data. In vitro acetylcholinesterase (AChE), butyrylcholinesterase (BuChE) inhibitory activity, antioxidant activity and cyclooxygenase (COX) inhibitory activity were investigated following standard spectrophotometric methods. Molecular docking studies to predict the binding mode with AChE and BuChE in addition to the pharmacokinetic profile of the synthesized compounds were studied with the help of online cheminformatics software. Results: Amongst the tested compounds for anticholinesterase activity, 4e and 4g hybrid derivatives were found to be the most potent AChE inhibitors (IC50 values = 29.56 and 28.68 μM), respectively. Compound 4m exhibited the maximum inhibitory activity against BuChE (IC50 value = 23.97 μM). Compounds 4g and 4e also showed higher selectivity index (SI) of 1.652 and 1.552 as compared to standard galantamine (SI = 1.132). Molecular docking studies revealed that 4g and 4e, two most potent AChE inhibitors identified through in vitro assay, binds well to AChE (binding energy scores of −9.7 and −10.1 Kcal/Mol). Synthesized hybrid molecules also exhibited good to excellent in vitro antioxidant and anti-inflammatory activities. Conclusion: Based on the results of in vitro and in-silico studies, it could be concluded that coumarin-oxadiazole hybrids acts as MTDLs and are promising source of anti-AD drugs. Further detailed investigations and modification of these compounds can lead to the development of highly potent therapeutics for the treatment of AD.